2018
DOI: 10.1007/s00167-018-5002-7
|View full text |Cite
|
Sign up to set email alerts
|

Implant preloading in extension reduces spring length change in dynamic intraligamentary stabilization: a biomechanical study on passive kinematics of the knee

Abstract: During passive flexion/extension, the highest spring shortening was consistently measured in full extension with a continuous decrease towards flexion. If preloading of the spring is performed in extension, the spring can be downsized to incorporate a maximum length change of 5 mm resulting in a smaller implant with less bone sacrifice and, therefore, improved conditions in case of revision surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The arthroscopic ACL repair technique with the most experimental and clinical data available is DIS [ 32 , 33 , 34 , 35 , 36 ]. Although several authors reported functional results comparable to our cohort, Ahmad et al reported low DIS survival rates (of only 70% at 5-year follow-up) and Osti et al reported a high rate of recurrent instability (of up to 17.5%) [ 22 , 32 , 35 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The arthroscopic ACL repair technique with the most experimental and clinical data available is DIS [ 32 , 33 , 34 , 35 , 36 ]. Although several authors reported functional results comparable to our cohort, Ahmad et al reported low DIS survival rates (of only 70% at 5-year follow-up) and Osti et al reported a high rate of recurrent instability (of up to 17.5%) [ 22 , 32 , 35 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a biomechanical study in the human cadaveric knee, Zavras et al found that even the slightest misplacement of tunnels away from a small isometric area within the ACL's femoral attachment, corresponding to one of two points central or anterior in the ACL's tibial attachment, led to length change during flexion of the knee [15]. Furthermore, Haberli et al, more recently, reported that in augmented ACL suture repair dispersion of tunnel positions of only a few millimetres around their associated isometric points could already lead to an increase of 4.0-20.9 mm of anterior tibial translation across the arc of flexion of the knee [11]. The extent of dispersion of the actual femoral and tibial tunnel positions -even when targeting for their associated isometric point -in the present study imply that isometric positioning of the augmentation braid is not reliable in augmented ACL suture repair.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of dispersion of the actual femoral and tibial tunnel positions -even when targeting for their associated isometric point -in the present study imply that isometric positioning of the augmentation braid is not reliable in augmented ACL suture repair. This leads to slackening/tightening of the augmentation braid across the arc of flexion of the knee, which leaves the suture-repaired ACL either unprotected or stretched; not only after static augmentation, but possibly also after dynamic augmentation, which can only compensate for 8 mm of length change [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations